Intensification of innovation activities in the Vologda region by organisation of joint project activity in the region’s higher education institutions - I. V. Krukova; A. A. Lagun (Вестник университета)
The article describes the experience of implementing a project approach to teaching in some universities of the Vologda region – Vologda State Agricultural Academy named after N.V. Vereshchagin and Cherepovets State University. The project approach is considered as the basis for the innovative development of educational institutions in the current context. The need for a project-based approach from the perspective of the student as an educational services consumer has been justified. The characteristics of the interaction forms between two universities in project activities are given, and the process of creating an inter-university project community during the pandemic of 2020-2021 is described. The creation of an inter-university project community is dictated by the need to develop methodological and practical tools to combine the educational potential of the two universities, as there is a demand for workers with a wide range of contemporary knowledge in today’s labour market. The tasks of university cooperation are outlined: organisation of interuniversity project teams; development of projects that include agricultural topics using contemporary technologies in the robotics field. The inter-university project community resulted in the merging of the two institutes’ disciplinary features and the development of two projects in the fields of biotechnology and agronomy with robotics processes.